Analysis of the methodology for controlling heat loss in buildings - Saydullaev Sirojiddin Rakhmatullaevich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
In order to minimize the heat loss of the building from maximum to minimum, the scientific article notes the main features of transferring a constant temperature to flow heaters at the same flow rate and transferring heat to a thermostatic valve. To minimize building heat losses, the installation of thermostatic valves in radiators is analyzed to compensate for the thermal effect caused by preventing excess temperature transfer.